Bismuth Oxide Prepared by Sol-Gel Method: Variation of Physicochemical Characteristics and Photocatalytic Activity Due to Difference in Calcination Temperature - Yayuk Astuti; Brigita Maria Listyani; Linda Suyati; Adi Darmawan (Indonesian Journal of Chemistry, 2021)
Research on synthesis of bismuth oxide (Bi2O3) using sol-gel method with varying calcination temperatures at 500, 600, and 700 °C has been done. This study aims to determine the effect of calcination temperature on the characteristics of the obtained products which encompasses crystal structure, surface morphology, band-gap energy, and photocatalytic activity for the decolorization of methyl orange dyes through its kinetic study. Bismuth oxide prepared by sol-gel method was undertaken by dissolving Bi(NO3)3·5H2O and citric acid in HNO3. The mixture was stirred then heated at 100 °C. The gel formed was dried in the oven and then calcined at 500, 600, and 700 °C for 5 h. The obtained products were a pale yellow powder, indicating the formation of bismuth oxide. This is confirmed by the existence of Bi–O and Bi–O–Bi functional groups through FTIR analysis. All three products possess the same mixed crystal structures of α-Bi2O3 (monoclinic) and γ-Bi2O3 (body center cubic), but their morphologies and band gap values are different. The higher the calcination temperature, the larger the particle size and the smaller the band gap value. The accumulative differences in characteristics appoint SG700 to have the highest photocatalytic activity compared to SG600 and SG500 as indicated by its percent degradation value and decolorization rate constant.